PROJETO DE TRANSPORTADORES PNEUMÁTICOS DE GRÃOS - Fonseca, Simão P. G. d. S.; Hartmann, Ricardo A.; Hoffmann, Roger S.; Rasia, Luiz A.; Valdiero, Antonio C.; Bortolaia, Luis A. (Salão do Conhecimento, 2013)
Resumo